Nonsurgical Treatment of Unusual Dens Invaginatus with MTA Based Filler in Immature Maxillary Lateral Incisor: A Case Report - Moazami, Fariborz; Sobhnamayan, Fereshte; Malekzadeh, Parastoo; Naseri, Mohammadhasan (Iranian Endodontic Journal, 2021)
Dens invaginatus (DI) is a dental anomaly associated with complex internal anatomy. Our article discusses an unusual maxillary lateral incisor with two DI. The treatment was planned and performed using cone-beam computed tomographic (CBCT) imaging. During clinical and radiographic evaluations, tooth #7 was diagnosed with DI and pulp necrosis with asymptomatic apical abscess. Periapical radiographs of the tooth showed 2 roots and complex internal anatomy. CBCT evaluation revealed tooth #7 had 2 separate cul-de-sacs (that separate the main canal into four portions). Root canal treatment was completed in 2 visits. The tooth was obturated with EndoSeal MTA. At the 6-month re-evaluation, the patient remained asymptomatic and his tooth had remained functional. Clinical and radiographic examination showed tooth #7 had no sensitivity to percussion or palpation, probe depths within normal limits (#3 mm), no mobility and continued improvement of periapical lesion, despite the commencement of orthodontic Rx 3months previous. Radiographic assessment at the one-year follow up showed signiﬁcant osseous healing of the preoperative lesion even after the orthodontic forces.